2020
DOI: 10.1007/s10584-020-02889-x
|View full text |Cite|
|
Sign up to set email alerts
|

Farmers’ perceptions and matching climate records jointly explain adaptation responses in four communities around Lake Tana, Ethiopia

Abstract: Farmers’ climate perceptions are responsible for shaping their adaptive responses and are thus essential to consider for the design of strategies to reduce vulnerability and increase resilience. In this study, we collected social data in four communities in the central Ethiopian Highlands on farmers’ climate perceptions and adaptations using group discussions and PRA tools. We related these to climate data spanning 30 years (1981 to 2010), consisting of daily minimum temperature, maximum temperature and precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 49 publications
0
21
1
Order By: Relevance
“…is indicated that though farmers in the study area had good perceptions of climate change and its impact, they had weak adaptive capacity. In line with this, Darabant et al [27] and Bekele et al [61] reported that though farmers' awareness of climate change had been improved through time, the level of adoption of different adaptation strategies to offset the negative impact of climate change is still low and external supports have to be provided. Furthermore, poverty, food insecurity, natural resources' degradation, high population growth, and poor social services pose multiple stresses on smallholder farmers and planned adaptation has to be implemented to strengthen the weak adaptive capacity of those people [62].…”
Section: Farmers' Perception Of Climate Change Its Impact and Eir Adaptationmentioning
confidence: 94%
See 2 more Smart Citations
“…is indicated that though farmers in the study area had good perceptions of climate change and its impact, they had weak adaptive capacity. In line with this, Darabant et al [27] and Bekele et al [61] reported that though farmers' awareness of climate change had been improved through time, the level of adoption of different adaptation strategies to offset the negative impact of climate change is still low and external supports have to be provided. Furthermore, poverty, food insecurity, natural resources' degradation, high population growth, and poor social services pose multiple stresses on smallholder farmers and planned adaptation has to be implemented to strengthen the weak adaptive capacity of those people [62].…”
Section: Farmers' Perception Of Climate Change Its Impact and Eir Adaptationmentioning
confidence: 94%
“…Moreover, Esayas et al [18] explained that farmers' perception of climate change is further influenced by social, economic, demographic, and institutional factors. us, for better planning and adoption of strategies to cope with the impacts of climate change, exploring farmers' perceptions linked with the analysis of climate data at a local level is vital [25,27].…”
Section: Farmers' Perceptions Of Climate Change Correspondence With Climate Trend Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…IPCC defines vulnerability as "the propensity or predisposition to be adversely affected" [32], which entails the degree to which a system is susceptible to adverse effects, the function of the magnitude and rate of climate variation, and the sensitivity and adaptive capacity of the system, resulting in a multidimensional concept that bridges biophysical and social aspects [33][34][35]. Several studies have proposed indicators to measure vulnerability, including location, socio-demographic aspects, and physical, social, human, and natural capital as the main components of exposure, sensitivity, and adaptive capacity, with the aim of identifying key components of vulnerability and/or relating it to adaptation behavior [34][35][36][37][38][39][40].…”
Section: Vulnerability To Climate Change and Adaptationmentioning
confidence: 99%
“…Several studies have proposed indicators to measure vulnerability, including location, socio-demographic aspects, and physical, social, human, and natural capital as the main components of exposure, sensitivity, and adaptive capacity, with the aim of identifying key components of vulnerability and/or relating it to adaptation behavior [34][35][36][37][38][39][40]. Nevertheless, in the literature, increasing attention has been given to perceived vulnerability and awareness of climate change [33,41,42], as it has been demonstrated that there is a strong link between perceptions and adaptation [11,[14][15][16][43][44][45][46]. Likewise, the relationship between perceived vulnerability and bio-physical data has also been studied and it was concluded that there is a positive trend between them [42,47].…”
Section: Vulnerability To Climate Change and Adaptationmentioning
confidence: 99%